Specific PCR Assay for Rapid and Direct Detection of Neisseria meningitidis in Cerebrospinal Fluid Specimens - M Qurbanalizadegan; R Ranjbar; RA Ataee; M Hajia; Z Goodarzi; S Farshad; N Jonaidi Jafari; Y Panahi; H Kohanzad; M Rahbar; H Ghadimi; M Izadi (Tehran University of Medical Sciences, 2010)
Background: Neisseria meninigitidis is one of the most frequently encountered microorganisms associated with central nervous system infections. The aim of this study was to evaluate a PCR-based assay for specific and rapid detection of N. meninigitidis in CSF specimens.  Methods: Since April 2002 to July 2006, 130 CSF specimens were collected from patients suspected of having bacterial meningitis. Bacterial isolation and identification was carried out according to the standard bacteriological methods.  The PCR was used to amplify a 101bp fragment of capsular transport gene A (ctrA) of N. meningitidis. Results: PCR yielded an amplified product with the expected size of 101 base pair fragment. Sensitivity test proved 500 ng of N. meningitidis DNA as the final detection limit and specificity test revealed no cross-reaction for a wide range of respiratory pathogenic organisms. Conclusion: The PCR assay was more sensitive than the bacterial culturing. It might be possible to apply this procedure for rapid diagnosis of meningococci in clinical samples.